The SAGE handbook of resistance - Courpasson, David; Vallas, Steven P. (Steven Peter) 1951- (Sage Publications, 2016)
"The SAGE Handbook of Resistance offers theoretical essays enabling readers to forge their own perspectives of what "is" resistance and emphasizes the empirical and experiential dimension of resistance - making strong choices in terms of how contemporary topics related to resistance help to rethink our societies as protest societies."--Amazon.com website.